ANALISIS INVESTASI PEMBANGUNAN PROYEK RUMAH SAKIT AL-ARAFAH KOTA KEDIRI - Muhammad Syahrul Aditrio; Wateno Oetomo (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
The review of a project helps to increase/select investment opportunities. Errors in choosing a project can result in sacrifice/loss of existing capital/resources. Therefore, careful evaluation is required before executing a project. The same thing is also needed for the construction project of the Al-Arafah Hospital in the City of Kediri. This project needs to analyze the feasibility of investment from several aspects including market and financial aspects. The reason for conducting an investment analysis for this project is that all investments have an expected return. This paper discusses the feasibility of investing in the construction project of the Al-Arafah Hospital in Kediri City in terms of market feasibility analysis and financial feasibility analysis with the parameters Net Present Value, Internal Rate of Return, Payback Period, and Break Even Point using Microsoft Excel. Judging from the analysis of the market and financial aspects, Al-Arafah Hospital, Kediri City, is feasible for development. Judging from the market aspect, Al-Arafah Hospital, Kediri City, has a better facility plan than its competitor hospitals. According to the tariff plan, Al-Arafah Hospital in Kediri City is considered cheaper compared to other hospitals in the same category. And the results of the analysis from the financial aspect are the Net Present Value (NPV) of Rp. 9,643,112,333 0, the value of the Benefit Cost Ratio (BCR) is 4.083 1, the value of the Internal Rate of Return shows an increase of 17.63% from the MARR of 12.0%, and with a Payback Period (PP) in the fifth year of the twenty-year investment period